2006
DOI: 10.1016/j.adolescence.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Parental communication and youth sexual behaviour

Abstract: The role of parental communication and instruction concerning sexual behaviour were studied in a community‐based sample of 1083 youth aged 13–17 (mean age of 15 years; 51% girls, 49% White). The Youth Asset Survey was administered along with items measuring demographics and youth risk behaviours. After controlling for demographic factors, multivariate analysis revealed that youth were much less likely to have initiated sexual intercourse if their parents taught them to say no, set clear rules, talked about wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
166
3
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(190 citation statements)
references
References 44 publications
12
166
3
9
Order By: Relevance
“…For example, a number of studies showed that parent-child communication about sexual issues is associated with delayed onset of sexual intercourse (e.g., Aspy et al, 2007;Lehr, DiIorio, Dudley, & Lipana, 2000), increased contraceptive use (including condom use), and fewer sexual partners (e.g., Holtzman & Rubinson, 1995;Pick & Palos, 1995).…”
Section: Theoretical Rationalementioning
confidence: 99%
“…For example, a number of studies showed that parent-child communication about sexual issues is associated with delayed onset of sexual intercourse (e.g., Aspy et al, 2007;Lehr, DiIorio, Dudley, & Lipana, 2000), increased contraceptive use (including condom use), and fewer sexual partners (e.g., Holtzman & Rubinson, 1995;Pick & Palos, 1995).…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Studies explored parental involvement [10,11], parental communication [12] parental monitoring [13], family processes [14], family health and dysfunction [15] family function [16] family interventions [17] and family structure [18]. For the purposes of this article the focus will be on family structure and the authors recognise that family structure is not static [19].…”
Section: Introductionmentioning
confidence: 99%
“…Budaya tabu, rasa malu dan kurangnya keterampilan komunikasi menghambat komunikasi antara orangtua-remaja tentang perilaku seksual (Ayalew, 2014). Remaja yang memiliki keyakinan positif dan terbuka dengan orangtua tentang seksualitas dapat mempengaruhi keputusan dalam berperilaku seksual (Schouten, 2007;Aspy, 2007) Variabel pendidikan orangtua memiliki hubungan dengan perilaku seksual remaja. Melalui komunikasi, orangtua seharusnya menjadi sumber informasi dan pendidik utama tentang seksualitas bagi remajanya.…”
Section: Variabelunclassified